Human Engineering: Predictors of Cognitive Ergonomics for Nurses - Rajini, G; Gomathi, K (International Journal of Engineering and Technology, 2018)
Background/Objectives: Ergonomics is becoming more of a priority in today’s work environment. Ergonomics is now focused on health care sector, where the environment has loaded the work for nurses. This in turn affects the quality of health care, and patient healing. This study focuses on analysing the role of work environment, task (job) and mental workload on nurses towards their personal well-being.Methods/Statistical analysis: This study was conducted at Chennai city a hub for medical tourism and multispecialty hospitals . The data were collected from 100 samples of Nurses in health care sector through Questionnaire  and a technique multiple regression analysis (Enter Method ) was applied to measure the combined effects of independent variables  on the dependent  softwarewith SPSS 21.0.Findings: The studies found that cognitive ergonomics depends significantly on mental workload and Work Environment. Whereas the Tasks done by Nurses have no significant dependency on cognitive ergonomics.